Conceptualising the criteria of the Islamic personality traits for Muslim medical imaging practitioners - Siti Maryam Muhamad Ruzlan, Siti Maryam; Zainuddin, Zainul Ibrahim (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2017)
Islamic Personality (IP) is a form of moral quality in the psychological aspects of a human which is governed by the belief in Allah as the One God and Prophet Muhammad (Peace be upon him) as His servant and His messenger. Many Muslim Personality tests have been established in order to understand the personality based on the principles in Islam. By adopting and adapting existing Muslim personality tests can help in formulating the criteria to measure the Islamic personality traits of Medical imaging students and practitioners. The Medical Imaging practice is comprised of various domains; basic principles in healthcare and medical imaging, patient care, use of technology, the technicalities or procedures, quality, safety, economic, research and professionalism. Thus, the IP can be different from other fields in health sciences. This paper examined various professional guidelines for Medical Imaging practitioners for some specific attributes for each domain in Medical Imaging practice. Among the attributes are, respectful; safe practice; safe activity; equality; trustworthy; honesty and integrity; truthful; responsible and accountable; compassionate; wisdom; being up-to-date; competence; teamwork; self-reflection; dignity; ethical behaviours; adhere to laws and regulations; effective communication; and continuity of knowledge and skills development. These attributes form the personality of the Medical Imaging practitioners. Previous studies have shown that there are positive connections between religiosity and the factor of personality. Religiosity, emotional religion and spirituality can be predicted through the assessment of personality factors. The formulation of a model for Islamic personality and its measures are very important in order to assess the characteristics of the Medical imaging graduates and practitioners, especially when it comes to matters of employment as well as the Islamisation of the professional and the profession. The benefits of the criteria formulation are seen within enhancement of the Medical imaging practice to what Islam champions.